2011
DOI: 10.1093/hmg/ddr120
|View full text |Cite
|
Sign up to set email alerts
|

Common genetic variants associated with open-angle glaucoma

Abstract: Open-angle glaucoma (glaucoma) is a major eye disorder characterized by optic disc pathology. Recent genome-wide association studies identified new loci associated with clinically relevant optic disc parameters, such as the optic disc area and vertical cup-disc ratio (VCDR). We examined to what extent these loci are involved in glaucoma. The loci studied include ATOH7, CDC7/TGFBR3 and SALL1 for optic disc area, and CDKN2B, SIX1, SCYL1/LTBP3, CHEK2, ATOH7 and DCLK1 for VCDR. We performed a meta-analysis using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
127
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(135 citation statements)
references
References 32 publications
8
127
0
Order By: Relevance
“…The SIX1-SIX6 locus was first identified as being associated with increased VCDR, which is considered as one of critical ocular biomarkers for the diagnosis of glaucoma and its progression to blindness (Ramdas et al, 2010). Several subsequent studies have also confirmed that the SIX1/SIX6 locus was significantly correlated with POAG and VCDR in different independent ethnic cohorts (Burdon et al, 2015;Chen et al, 2015;Fan et al, 2011;Iglesias et al, 2014;Mabuchi et al, 2015;Osman et al, 2012b;Philomenadin et al, 2015;Ramdas et al, 2011;Wiggs et al, 2012), but the association has not yet been demonstrated in African cohorts owing to the high frequency of the risk allele both in patients and controls (Liu et al, 2013;Williams et al, 2015). Recently, two population-based studies using cohorts from Singapore and of European-descents showed that both glaucomatous and nonglaucomatous subjects with risk allele variants in the SIX1/SIX6 locus (rs10483727 and rs33912345) were susceptible to thinner retinal nerve fiber layer thickness, which confirmed the results of previous studies (Carnes et al, 2014;Cheng et al, 2015;Kuo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The SIX1-SIX6 locus was first identified as being associated with increased VCDR, which is considered as one of critical ocular biomarkers for the diagnosis of glaucoma and its progression to blindness (Ramdas et al, 2010). Several subsequent studies have also confirmed that the SIX1/SIX6 locus was significantly correlated with POAG and VCDR in different independent ethnic cohorts (Burdon et al, 2015;Chen et al, 2015;Fan et al, 2011;Iglesias et al, 2014;Mabuchi et al, 2015;Osman et al, 2012b;Philomenadin et al, 2015;Ramdas et al, 2011;Wiggs et al, 2012), but the association has not yet been demonstrated in African cohorts owing to the high frequency of the risk allele both in patients and controls (Liu et al, 2013;Williams et al, 2015). Recently, two population-based studies using cohorts from Singapore and of European-descents showed that both glaucomatous and nonglaucomatous subjects with risk allele variants in the SIX1/SIX6 locus (rs10483727 and rs33912345) were susceptible to thinner retinal nerve fiber layer thickness, which confirmed the results of previous studies (Carnes et al, 2014;Cheng et al, 2015;Kuo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several POAG susceptibility loci were identified by genome-wide association (GWA) studies [16][17][18][19][20] and were replicated in multiple ethnicities: 7q31.2 between CAV1 and CAV2, 16,21 9p21.3 with CDKN2B-AS1, 19,20,[22][23][24][25][26] 10q21.3 with ATOH7, 17,18,22,27 and 14q23.1 between SIX1 and SIX6. 17,20,22,28 One of the GWA studies demonstrated the association of POAG with six SNPs that flanked the ZP4, PLXDC2, and TMTC2 genes located at chromosome loci 1q43, 10p12.31, and 12q21.31, respectively, in a Japanese population; 29 however, these associations were not replicated in a South Indian, 30 Afro-Caribbean, 24 or Chinese 31 population.…”
Section: Introductionmentioning
confidence: 99%
“…17,20,22,28 One of the GWA studies demonstrated the association of POAG with six SNPs that flanked the ZP4, PLXDC2, and TMTC2 genes located at chromosome loci 1q43, 10p12.31, and 12q21.31, respectively, in a Japanese population; 29 however, these associations were not replicated in a South Indian, 30 Afro-Caribbean, 24 or Chinese 31 population. These conflicting results can be ascribed to factors such as a small sample size with inadequate statistical power, different phenotype definitions, population-specific linkage disequilibrium (LD), effect-size bias, or population stratification.…”
Section: Introductionmentioning
confidence: 99%
“…98 The most common condition related to optic disc parameters is of course glaucoma. Ramdas et al 99 performed a meta-analysis, investigating SNPs found to be related to optic disc parameters in populations of POAG upon whom GWAS have been completed. Of particular interest, they confirmed three loci associated with optic disc parameters also having an association with POAG.…”
Section: Optic Disc Parametersmentioning
confidence: 99%